Autoantibodies in COVID-19: implications for disease severity and clinical outcomes - Galipeau, Yannick; Cooper, Curtis; Langlois, Marc-André (Frontiers in Immunology, 2025)
Few pathogens have historically been subjected to as intense scientific and clinical scrutiny as SARS-CoV-2. The genetic, immunological, and environmental factors influencing disease severity and post-infection clinical outcomes, known as correlates of immunity, remain largely undefined. Clinical outcomes of SARS-CoV-2 infection vary widely, ranging from asymptomatic cases to those with life-threatening COVID-19 symptoms. While most infected individuals return to their former health and fitness within a few weeks, some develop debilitating chronic symptoms, referred to as long-COVID. Autoimmune responses have been proposed as one of the factors influencing long-COVID and the severity of SARS-CoV-2 infection. The association between viral infections and autoimmune pathologies is not new. Viruses such as Epstein-Barr virus and cytomegalovirus, among others, have been shown to induce the production of autoantibodies and the onset of autoimmune conditions. Given the extensive literature on SARS-CoV-2, here we review current evidence on SARS-CoV-2-induced autoimmune pathologies, with a focus on autoantibodies. We closely examine mechanisms driving autoantibody production, particularly their connection with disease severity and long-COVID.